Gallbladder perforation as a rare complication of minor blunt abdominal trauma: a case report - Haddis Birhanu W/kiros; Ashenafi Amsalu Feleke; Kidanemariam Mulualem Alamir; Temesgen Agegnehu Abebe; Wudie mekonen Alemu; Shimelis Seid Tegegne; Habtu Adane Aytolign (Patient Safety in Surgery)
Abstract Background Blunt abdominal trauma leading to gallbladder injury is rare and presents a diagnostic challenge. Here, we present scenario of gallbladder perforation due a blow from a fist to the abdomen. Case presentation A 30-years old male patient was admitted to University of Gondar comprehensive specialized hospital emergency department in Ethiopia due to blow from a fist on the right upper abdomen with a presumptive diagnosis of generalized peritonitis and underwent emergency laparotomy. The operative finding showed that, gallbladder was perforated at the fundus and a cholecystectomy was done. Postoperative time was uneventful and discharged on the 5th postoperative day. Conclusion Isolated gallbladder injury from a fist fight is rare, however, should be considered in the differential diagnosis of patients presenting with abdominal pain following minor blunt abdominal trauma.